2017
DOI: 10.1111/ner.12563
|View full text |Cite
|
Sign up to set email alerts
|

10 kHz High-Frequency Spinal Cord Stimulation for Chronic Axial Low Back Pain in Patients With No History of Spinal Surgery: A Preliminary, Prospective, Open Label and Proof-of-Concept Study

Abstract: HF10 therapy may provide significant back pain relief, reduction in disability, improvement quality of life, and reduction in opioid use in chronic low back pain not resulting from spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 35 publications
7
91
0
Order By: Relevance
“…Overall, 10 kHz SCS has shown potential in treating types of chronic pain, including low back pain and neuropathic pain, that are often unresponsive to conventional medical treatments. Prospective, nonrandomized trials of 10 kHz SCS in patients with chronic back pain reported pain relief ranging from 54% to 87% after at least 1 year of treatment, and leg pain scores similarly improved by 57% to 72% in these patients . The mean daily dose of conventional opioids required by patients in these studies was halved or more after 10 kHz SCS treatment, and the number of opioid‐abstinent subjects increased in all the studies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, 10 kHz SCS has shown potential in treating types of chronic pain, including low back pain and neuropathic pain, that are often unresponsive to conventional medical treatments. Prospective, nonrandomized trials of 10 kHz SCS in patients with chronic back pain reported pain relief ranging from 54% to 87% after at least 1 year of treatment, and leg pain scores similarly improved by 57% to 72% in these patients . The mean daily dose of conventional opioids required by patients in these studies was halved or more after 10 kHz SCS treatment, and the number of opioid‐abstinent subjects increased in all the studies.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, in their analysis of the SENZA‐RCT results, the authors concluded that the significant benefits and low risks of 10 kHz SCS relative to alternative treatments suggested that economic benefits might be associated with this treatment modality . Likewise, other investigators suggested that improvements in quality of life measures or reductions in conventional opioid use should result in lower long‐term healthcare costs. Finally, the finding by DiBenedetto and colleagues that patients treated with 10 kHz SCS required fewer interventional procedures than matched controls provides further support for the possible financial benefits of the treatment …”
Section: Explantsmentioning
confidence: 99%
“…In subjects with chronic, severe, low back pain who were not candidates for spinal surgery and were naïve to surgery, the 12-month response rate in the prospective study by Al-Kaisy and colleagues was strikingly high. 57 The results suggest that 10 kHz SCS may be a viable option in this population where treatment possibilities are limited. Promising reductions in pain were also found in retrospective studies of neuropathic limb pain, chronic widespread pain, and CRPS.…”
Section: Discussionmentioning
confidence: 91%
“…The benefits of 10 kHz SCS therapy for subjects with chronic back pain ineligible for spinal surgery and no history of such intervention were evaluated in a separate, single‐center, prospective study by Al‐Kaisy and colleagues . Twenty of 21 enrolled subjects (95%) had a successful trial, received an implantable pulse generator, and completed 12 months of follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation